Vascularized interpositional periosteal connective tissue flap: A modern approach to augment soft tissue - Chitra Agarwal; Savita Deora; Dennis Abrahm; Rohini Gaba; Baron Tarun Kumar; Praveen Kudva (Wolters Kluwer Medknow Publications, 2015)
Context: Nowadays esthetics plays an important role in dentistry along with function of the prosthesis. Various soft tissue augmentation procedures are available to correct the ridge defects in the anterior region. The newer technique, vascularized interpositional periosteal connective tissue (VIP-CT) flap has been introduced, which has the potential to augment predictable amount of tissue and has many benefits when compared to other techniques. Aim: The study was designed to determine the efficacy of the VIP-CT flap in augmenting the ridge defect. Materials and Methods: Ten patients with Class III (Seibert's) ridge defects were treated with VIP-CT flap technique before fabricating fixed partial denture. Height and width of the ridge defects were measured before and after the procedure. Subsequent follow-up was done every 3 months for 1-year. Statistical Analysis Used: Paired t-test was performed to detect the significance of the procedure. Results: The surgical site healed uneventfully. The predictable amount of soft tissue augmentation had been achieved with the procedure. The increase in height and width of the ridge was statistically highly significant. Conclusion: The VIP-CT flap technique was effective in augmenting the soft tissue in esthetic area that remained stable over a long period.